Identification of polymorphic allozyme markersfor population structure analysis in Horabagrusbrachysoma (Gunther, 1864). - Gopalakrishnan, A; Muneer, P M Abdul; Thomas, P C; Lal, Kuldeep Kumar; Mohindra, Vindhya; Basheer, V S; Kapoor, D; Ponniah, A G (Indian Journal of Fisheries, 2014)
Fourteen polymorphic allozyme loci were identified in yellow catfish, Horabagrusbrachysoma. The genetic variation detected at each allozyme locus was assessedfor samples collected from three rivers. The observed heterozygosities per locusranged from 0.0286 to 0.4000. Significant genotype heterogeneity indicated thatthe samples are not drawn from same gene pool. The results suggest the potentialof the identified loci to analyze stock structure of natural populations of H. brachysoma.